Evaluation of apoptosis in skin biopsies of patients of borderline leprosy and lepra type 1 reaction - Nivedita Patnaik; Sarla Agarwal; Sonal Sharma; Satendra Sharma; Deepika Pandhi (Wolters Kluwer Medknow Publications, 2015)
Background: The role of apoptosis is not clear in leprosy and lepra reactions. Objectives: To evaluate frequency of apoptosis in skin lesions of borderline leprosy and Type 1 lepra reaction. Methods: Sixty patients with borderline leprosy (30 with clinically diagnosed Type 1 reaction (T1R) (Group I) and 30 without clinical evidence of reaction (Group II)) were analyzed in this prospective study. Apoptosis was detected by two different methods for comparison, that is, histopathologic examination (HPE) and deoxyribonucleic acid (DNA) fragmentation and electrophoresis. Quantification of apoptotic bodies/10 high power fields (HPF) was also done. Results: Out of 30 cases, apoptosis was detected in 29 cases in Group I and 24 cases in Group II by HPE (P = 0.103), whereas, with the use of DNA electrophoresis it was detected in 24 cases in Group I and 18 cases in Group II (P = 0.091). On quantitative estimation it was found that number of apoptotic bodies are higher in Group I in comparison to Group II (2.77 vs 1.99), which is statistically significant. Conclusions: There was moderate agreement (κ = 0.47) between the two methods of apoptosis detection. Apoptosis was seen more in patients with T1R both qualitatively (statistically nonsignificant) and quantitatively (statistically significant). Clinical significance of this novel finding is that apoptosis can be used as one of the variables for diagnosis of T1R to increase detection rate.